Sistem Pengelolaan Pariwisata Bertema Agrowisata Bhakti Farm – Biodynamic Garden Di Tampak Siring, Kabupaten Gianyar, Bali - Oni, David Putra Maoekari Van; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p09, 2023)
Bhakti Farm – Biodynamic Garden is one of Bali’s Agrotourism sites that has caught due to massive, ongoing tourism development model. The purpose of this study was to determine the management system for Bhakti Farm – Biodynamic Garden as a tourist attraction in Tampak Siring, Gianyar Regency, Bali. The background underlying this study is Agrotourism of Bhakti Farm – Biodynamic Garden. The type of data used is qualitative data with the source of primary and secondary. Analysis of the data used by the process of descriptive qualitative. Daya obtained through observation, literature study, and interview, and documentation. The theory used in this study is the POAC (planning, organizing, actuating, controlling). Results from this study is strength of a leaders and managers of tourism attractions in executing management functions POAC management system as well as it has been implemented in Bhakti Farm – Biodynamic Garden. Good management has a positive impact on managers such as numbers of tourists and volunteers are increase, good income, and sustainable tourism. Keywords: POAC, System Management, Agrotourism, Tourism Attraction